Osteointegration with implant and factors of it’s violation (literature review) - Bondarenko, Stanislav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2018)
Biological fixation of the hip joint endoprosthesis today plays an important role in cementless total hip arthroplasty. The duration of stable fixation of endoprosthesis components largely depends on the osseointegration of bone tissue into the implant. Objective: to determine the features of osseointegration around the implant and to identify the risk factors which affect this process. Methods: more than 40 works from electronic databases PubMed, Medline, as well as abstracts, articles and other sources of scientific and medical information were analyzed. Results: on the basis of the received information, the following issues were investigated: mechanisms and stages of osseointegration, factors affecting peri-implantation osteogenesis and osseointegration at arthroplasty. Osteointegration goes through the following stages: the inflammation, migration and differentiation of osteogenic cells, the formation of bone tissue, in which the surface of the implant is surrounded by an osteoid and a mineralized matrix; and bone tissue remodeling. Factors affecting peri-implantation osteogenesis and osseointegration in arthroplasty are also outlined. The following risk factors negatively influencing the process of osseointegration are highlighted: decrease in the amount or activity of osteoblasts, increase in the density of osteoclasts, imbalance between local and systemic factors affecting the formation and remodeling of the bone, violation of vascularization as a key factor affecting the differentiation of osteogenic cells. Conclusions: it was established that the implant surface has a great importance in the process of osseointegration: its composition, technological characteristics, hydrophilicity or hydrophobicity in the biological environment, tropicity to cells and possibility to perform their main function — the expression of the products of genes forming a macromolecular environment between the implant and the bone, followed by mineralization and characteristic structure.